Eco-Friendly Production of Iron Nanoparticles from Trigonella foenum-graecum Extract for Photo-Catalytic Methylene Blue Dye Degradation: Produksi Nanopartikel Besi Ramah Lingkungan dari Ekstrak Trigonella foenum-graecum untuk Degradasi Pewarna Metilen Biru secara Foto-Katalitik - Ahmed Makki Sadaa; Ihab Assad Altameemi; Ali Zabon Salman; Bassam Ashoor Al Abdul Aziz; Zainab taha Al Abdullah (Academia Open, 2025)
The huge surface area, redox characteristics, and magnetic properties of iron nanoparticles make them special. Iron sulphate (FeSO4) was used as a precursor to create iron nanoparticles, while Trigonella foenum-graecum was used as a reducing agent. There are a few more plant substitutes. Trigonella foenum-graecum is preferred over other plants because it is non-toxic, possesses exceptional antioxidant qualities, and stays stable at 60 °C when disturbed. The UV-Vis spectra showed the surface plasmon band (SPB) for iron nanoparticle formation at 430 nm. Iron nanoparticles with sizes in the range ( 23–77) nm and 50 nm, respectively, were visible in the pictures from the scanning electron microscope (SEM) and transmission electron microscopy (TEM). Methylene blue, a model substance for contaminated water, was broken down by the produced iron nanoparticles at a wavelength of 663 nm. Additionally, its deterioration was investigated to gauge the photocatalytic performance of the samples. These results showed that iron nanoparticles had a significant level of photocatalytic activity, reaching up to 56% in a one hour. Highlights: Iron nanoparticles: large surface, redox, magnetic, photocatalytic properties. Trigonella foenum-graecum: non-toxic, antioxidant, stable reducing agent. Photocatalytic activity: 56% methylene blue degradation in 1 hour Keywords: Degradation; Iron nanoparticle; Methylene blue dye; Water treatment